1-O-Tigloyl-1-O-deacetyl-nimbolinin B Inhibits LPS-Stimulated Inflammatory Responses by Suppressing NF-κB and JNK Activation in Microglia Cells - Li Tao; Fali Zhang; Lili Hao; Jing Wu; Jia Jia; Jiang-yun Liu; Long Tai Zheng; Xuechu Zhen (Elsevier, 2014)
Abstract.: Overactivation of microglia may contribute to the pathogenesis of neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, and HIV dementia. Thus, regulating microglial activation has been an important therapeutic strategy for treating neurodegenerative diseases. In this research, we compared three limonoids compounds extracted from Melia toosendan by a cell-based assay to investigate their anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated microglia cells. Our study indicated that 1-O-tigloyl-1-O-deacetyl-nimbolinin B (TNB) markedly suppressed the production of nitric oxide (NO) and tumor necrosis factor (TNF)-α in LPS-stimulated microglia cells. TNB also inhibited the gene expression of inducible nitric oxide synthase (iNOS), TNF-α, cyclooxygenase (COX-2), and interleukin (IL)-1β. In addition, TNB inhibited generation of intracellular reactive oxygen species (ROS). We found that TNB significantly attenuated the nuclear translocation of NF-κB, inhibiting the activation of c-jun N-terminal kinase (JNK) in LPS-stimulated BV-2 cells. Furthermore, TNB reduced cytotoxicity of activated microglia toward HT-22 hippocampal cells in a co-culture system. Taken together, our experimental results reveal, for the first time, that TNB is a potent inhibitor of microglia-mediated inflammation, and it might be a potential candidate for the treatment of neurodegenerative diseases. Keywords:: microglia, inflammation, 1-O-tigloyl-1-O-deacetyl-nimbolinin B, neuroprotection, lipopolysaccharide